تخصيص عام النص بالعُرف: مفهومه، حُجيّته، أقسامه، وأثره في استنباط الأحكام الشّرعيّة - عزام, إسماعيل (جامعة الوادي - University of Eloued, 2021)
تُفهم النصوص الشرعية بحسب مدلولاتها اللغوية والعرفية في زمن صدور النص الشرعي، وإنْ تعارض العرف مع النص وجب النظر في حقيقة هذا التعارض ومستواه، كليًا كان أو جزئيًا، فإن كان التعارض كليًا بحيث يلزم- إن عُمل بالعرف- تعطيل النص ورفع حكمه؛ ففي هذه الحالة يكون العرف فاسدًا ولا يجوز العمل به بحال من الأحوال، وإن كان التعارض جزئيًا، كأن يكون النص عامًا وعارضه عرفٌ في بعض أفراده، كأن يكون للناس عادة في تعاملهم ببعض ما تناوله ذلك اللفظ العام ،أو طرأ بعد النص العام عرف يخالف النص في بعض مدلولاته، أو كان هناك عرف قولي سابق للعام أو مقارن له في الظهور يتعارض معه في بعض أفراده، ففي مثل هذه الحالات يكون العرف مخصصًا للنص العام. ولا شك أن لتخصيص عام النص بالعرف أثرًا في استنباط الأحكام الشرعية في مسائل كثيرة سنبينها في طيات هذا البحث إن شاء الله. وتشير هذه الدراسة بإيجاز إلى لفظ العام من حيث: تعريفه، وأنواعه، ومخصصاته، ثم تتناول العرف: تعريفه من حيث: أنواعه وشروطه وأسبابه وأقسامه، وأثر التخصيص في العرف في تغيّر الأحكام الشرعية في الفقه الإسلامي، مرجحةً الرأي القائل بجواز تخصيص عام النص بكلٍّ من العرف القولي والعملي على حد سواء، وذلك من خلال التطبيقات المعاصرة : Religious texts shall be understood in terms of their linguistic and customary meanings at the time of the issuance of the text. If customs are contrary to the text, the fact and level of this conflict must be considered, whether in whole or in part. If that conflict is complete, the text must be invalidated and its provisions must be lifted when the custom applies. In this case, the custom is corrupt and may not be applied in any case. Although the conflict may be partial, such as: the text is general and opposed by the some individuals in some of its parts. For example, people used to deal with some of what that general text deals with ،or after the general text there has been a custom that contravenes the text in some of its meanings, or there is an earlier conventional or conventional custom that appears to contradict the text in some parts, then in such cases the custom is specialized for the general text. There is no doubt that customizing the general text by custom has an effect on inference religious texts on many matters. We will explain them in this paper. The present study briefly refers to the term general: its definition, types and attributions ،it also refers to custom: definition of custom: types, conditions, causes and divisions, and the effect of custom on the change of the provisions in Islamic jurisprudence. favouring the view that general provision may be allocated to both verbal and practical customs. by contemporary applications.
Customization of General Text by Custom: Its concept, Authoritative Power, Divisions, and Effect on Devising Sharia Rules
مقال
Keywords: التخصيص ; العام ; النص ; العرف ; الأحكام الشرعية; specialty; general; text; custom; legal judgments